Trust in government: lessons from the Clinton impeachment - Koven, Steven G.; Kunselman, Julie C. (2003)
The impeachment of Bill Clinton represented a major event in the nation's history. It marked the first time that an elected president was impeached in America's more than two hundred-year history. The process captivated attention for over one year and its implications will be debated for many decades into the future. This paper discusses the impeachment within the context of broad administrative themes. In addition, the impact of the Clinton impeachment on major institutions is addressed. tentative conclusions are finally offered in regard to impeachment's impact on trust in government. - Reproduced.
Keywords: Presidents - United States; Presidents